Is poor coordination of saccades in dyslexics a consequence of reading difficulties? A study case - Elham Ghassemi; Zoë Kapoula (Journal of Eye Movement Research)
We hypothesize that the high quality of binocular coordination of saccades in reading is progressively learned during childhood, and this oculomotor learning is based on a synergy between saccades and vergence. In present work deficits in the binocular control of saccades in six dyslexic children (mean age was 11±2.48 years) are studied for two tasks (text reading and Xs-C scanning), and at two viewing distances (40 cm and 100 cm). Fixation durations resulting are longer in Xs-C scanning task than in text reading task. We postulate that while reading motor preparation processes are executed with less demand for attentional resources. Importantly all physiological parameters of the saccades were the same for the two conditions and in either distance. Namely disconjugacy of saccades and disconjugate post-saccadic drifts were high but similar for the two conditions. Time analysis applied on saccade amplitude disconjugacy, on disconjugate post-saccadic drift and on fixation duration showed no significant effect of repetition or time. we believe that the binocular coordination deficits in dyslexic children reflect some type of microdyspraxia due to reduced oculomotor learning, perhaps related to inefficiency of the magnocellular visual system and the cerebellar functions.